The Hidden Powers of Glomalin: Insights into Soil Health and Functionality - , Vijayakumari Raveendra Channavar, Jakir Hussain K N, Ryali Devi Veda Vyas, Nagaraj Malappannavar, Varsha Somaraddi Radder, Jagadeesh B R (Archives of Current Research International, 2024)
Agricultural practices such as the application of inorganic fertilizers and pesticides have profound effects on soil, altering its physical and chemical properties and consequently impacting soil biota composition and diversity. Since plant health is intricately linked to soil health, managing soil in a manner that conserves and enhances soil biota can significantly improve crop yield and quality. The rhizosphere, the zone directly influenced by plant roots, harbours high populations of active microorganisms and plays a vital role in plant-microbe interactions. One of the most crucial symbiotic relationships in the rhizosphere is between plants and arbuscular mycorrhizal fungi (AMF). AMF form mutualistic associations with the roots of various plant species, including major crops and contribute to defence against soil-borne pathogens, nutrient cycling and soil aggregation. Glomalin, a glycoprotein secreted by AMF, plays a crucial role in soil aggregation, stability and carbon sequestration. It enhances soil structure, binds with soil particles, stabilizes aggregates and promotes water infiltration and retention. It also plays a role in sequestering toxic metals, reducing their availability to plants and mitigating their harmful effects on soil biota. Managing glomalin in soil involves practices such as minimizing tillage to preserve the hyphal network, maintaining living roots through cover crops to sustain fungal colonization and optimizing nutrient inputs to support fungal activity without overloading the soil. AMF and glomalin play pivotal roles in agricultural sustainability and soil ecosystem functioning, highlighting the importance of conserving and enhancing these beneficial microbial associations for improved soil health and crop productivity.